Assessment of strategies for male involvement in the prevention of mother-to-child transmission of HIV services in Blantyre, Malawi - Nyondo, Alinane Linda (Co-Action Publishing, 2013)
BACKGROUND: Despite the documented benefits of prevention of mother-to-child transmission (PMTCT) of human immunodeficiency virus (HIV) services, the uptake remains low in sub-Saharan Africa. The lack of male involvement (MI) may be one of the reasons for this. However, there are limited data on strategies for MI in PMTCT. OBJECTIVE: The objective of this study was to identify strategies that may promote MI in PMTCT services in antenatal care (ANC) services in Blantyre, Malawi. STUDY DESIGN: An exploratory qualitative study was conducted from December 2012 to January 2013 at South Lunzu Health Centre (SLHC) in Blantyre, Malawi. It consisted of six face-to-face key informant interviews (KIIs) with healthcare workers and four focus group discussions (FGDs) with 18 men and 17 pregnant women attending ANC at SLHC. The FGDs were divided according to sex and age. All FGDs and KIIs were digitally recorded and simultaneously transcribed and translated verbatim into English. Data were analyzed using thematic content analysis. RESULTS: Three major themes with several subcategories emerged. Theme 1 was a gatekeeping strategy with two subcategories: (1) healthcare workers refusing service provision to women accessing antenatal clinic without their partners and (2) women refusing ANC attention in the absence of a partner. Theme 2 comprised extending invitations and had six subcategories: (1) word of mouth, (2) card invites, (3) woman's health passport book invites, (4) telephonic invites, (5) use of influential people, and (6) home visits. Theme 3 was information education and communication, such as health education forums and advertisements. Of all the strategies, an invitation card addressed to the male partner was most preferred by study participants. CONCLUSIONS: There are several strategies by which men may be involved in PMTCT. Healthcare workers should offer a pregnant woman all strategies available for MI for her to select the appropriate one. Further research and consultations with men should continue to achieve higher levels of MI.